Targets for Antiviral Therapy of Hepatitis C - Rupp, Daniel; Bartenschlager, Ralf (Seminars in Liver Disease, 2014)
Presently, interferon- (IFN-) containing treatment regimens are the standard of care for patients with hepatitis C virus (HCV) infections. Although this therapy eliminates the virus in a substantial proportion of patients, it has numerous side effects and contraindications. Recent approval of telaprevir and boceprevir, targeting the protease residing in nonstructural protein 3 (NS3) of the HCV genome, increased therapy success when given in combination with pegylated IFN and ribavirin, but side effects are more frequent and the management of treatment is complex. This situation will change soon with the introduction of new highly potent direct-acting antivirals. They target, in addition to the NS3 protease, NS5A, which is required for RNA replication and virion assembly and the NS5B RNA-dependent RNA polymerase. Moreover, host-cell factors such as cyclophilin A or microRNA-122, essential for HCV replication, have been pursued as therapeutic targets. In this review, the authors briefly summarize the main features of viral and cellular factors involved in HCV replication that are utilized as therapy targets for chronic hepatitis C.
Keywords: NS3 protease; NS5A; NS5B; miR-122; cyclophilin A